Mortality after hip fractures in Thailand - Chariyalertsak S. (2014)
Hip fractures have long been considered a major threat to the survival of elderly people. Most of the studies on survival following hip fractures have been reported from developed countries where orthopedic care is well distributed. This report describes the survival experience of 330 elderly hip fracture patients who were seen at hospitals in Chiang Mai, Thailand. The mortality rate during hospitalization was 2.1%. The 3-, 6-, and 12-month survival rates after hip fractures were 91%, 88% and 83%, respectively. The significant predictors of mortality were male sex, age over 80 years, presence of chronic illnesses, poor pre-fracture walking ability, and nonoperative treatment.